CREATION OF E- COURSE TITLED ``COMPUTER FOR SENIORS'' - KOPRDA, Stefan; BRECKA, Peter (Trends in education, 2008)
There are many occasions when we meet with terms such e-learning, distance learning, flexible learning, online and offline learning etc. It is very important to focus on the one of e-learning basic components - e-courses. The way of creating of such course is different from the writing of the plain text. We focused on the creation of the e-course in the environment of MS Class Server. Its theme is the work with ICT (PC, Internet, e-mail) for seniors.
Keywords: e - course; Class Server; education.